Research progress on exosomes in podocyte injury associated with diabetic kidney disease - Li, Jiao; Zheng, Shanshan; Ma, Chaoqun; Chen, Xuexun; Li, Xuan; Li, Shengjie; Wang, Ping; Chen, Ping; Wang, Zunsong; Li, Wenbin; Liu, Yipeng (Frontiers in Endocrinology, 2023)
Diabetic kidney disease (DKD), a common cause of end-stage renal disease, is a serious complication that develops with the progression of chronic diabetes. Its main clinical manifestations are persistent proteinuria and/or a progressive decline in the estimated glomerular filtration rate. Podocytes, terminally differentiated glomerular visceral epithelial cells, constitute the glomerular filtration barrier together with the basement membrane and endothelial cells, and the structural and functional barrier integrity is closely related to proteinuria. In recent years, an increasing number of studies have confirmed that podocyte injury is the central target of the occurrence and development of DKD, and research on exosomes in podocyte injury associated with DKD has also made great progress. The aim of this review is to comprehensively describe the potential diagnostic value of exosomes in podocyte injury associated with DKD, analyze the mechanism by which exosomes realize the communication between podocytes and other types of cells and discuss the possibility of exosomes as targeted therapy drug carriers to provide new targets for and insights into delaying the progression of and treating DKD.